The implementation of public policies by the Peruvian state to face the impact of COVID-19 on violence against women and domestic violence - Huaita Alegre, Marcela (2021)
In this article, the authors analyze the response of the Peruvian State through the implementation of public policies with the aim of counteracting violence against women and members of the family group, triggered by the context of the COVID-19 pandemic.  Initially, the authors study the measures taken immediately by the Peruvian State during the start of the pandemic and place them in the Latin American context through a comparative perspective. Secondly, these measures are analyzed in detail in order to evaluate the limits and success in the effective implementation of said policies during the first year of the pandemic.